Cystic Fibrosis Isolates of Pseudomonas aeruginosa Retain Iron-Regulated Antimicrobial Activity against Staphylococcus aureus through the Action of Multiple Alkylquinolones - Nguyen, Angela T.; Jones, Jace W.; Cámara, Miguel; Williams, Paul; Kane, Maureen A.; Oglesby-Sherrouse, Amanda G. (Frontiers in Microbiology, 2016)
Cystic fibrosis (CF) is a hereditary disease that predisposes individuals to pulmonary dysfunction and chronic infections. Early infection of the CF lung with Staphylococcus aureus is common, while Pseudomonas aeruginosa becomes dominant as disease progresses. Emergence of P. aeruginosa likely depends on the action of multiple 2-alkyl-4-(1H)-quinolones (AQ) secreted by this organism. We recently showed that antimicrobial activity against S. aureus is enhanced by iron depletion and is dependent upon multiple AQ metabolites. Two of these AQs, the Pseudomonas quinolone signal (PQS; 2-heptyl-3-hydroxy-4(1H)-quinolone) and 2-heptyl-4-hydroxyquinoline (HHQ), are quorum sensing molecules that activate the expression of multiple microbicidal factors. Here we show for the first time that HHQ also exhibits innate antimicrobial activity against S. aureus. We further show that iron depletion potentiates the antistaphylococcal activity of HHQ, as well as 2-heptyl-4-hydroxyquinoline-N-oxide (HQNO), another AQ that functions as a cytochrome B inhibitor. Notably, we found that deletion of the genes for the terminal biosynthetic steps for either PQS or HQNO results in overproduction of the HHQ intermediate, likely maintaining the ability of these mutants to mediate antimicrobial activity. Compensatory increases in HHQ were also observed in PQS-deficient CF isolates, which also retained the ability to mediate iron-regulated antimicrobial activity against S. aureus. These studies demonstrate that iron-regulated antimicrobial activity of P. aeruginosa against S. aureus is due to the cumulative effects of multiple AQ metabolites, both the production and activity of which are modulated by environmental iron levels.